Empty bed blues - Garrett, George, 1929-2008 (University of Missouri Press, 2006)
"Garrett 's eighth collection of short fiction includes fifteen stories that blend fact and fiction, comedy and pathos, and the voices of diverse characters while focusing on the themes of love and death as well as the complexities of human relations"--Provided by publisher.